Fiscal Equalisation and the Soft Budget Constraint - Robert C. Plachta (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2008)
This paper assesses the interactions of horizontal fiscal equalisation schemes with debt policy by sovereign regional governments. Local public goods are either financed by debt or taxation. A horizontal equalisation scheme eleviates regional public revenue disparities under horizontal and vertical tax competition. We show that fiscal equalisation schemes have no impact on the optimal central government grant whereas they can either soften or harden the regional budget constraint depending on the specific formulae. Revenue equalisation softens the budget constraint whereas tax base equalisation hardens the budget constraint of poor states.
Keywords: H7; E62; 330; Fiscal federalism; public debt; soft budget constraint; fiscal equalisation; tax competition; Horizontaler Finanzausgleich; Finanzföderalismus; Länderfinanzen; Budgetrestriktion; Steuerwettbewerb; Öffentliche Schulden; Theorie